Epidemiological profile of acute Chagas disease in Brazil (Research, Society and Development, 2023)
The study aims to characterize the epidemiological profile of acute Chagas disease in Brazil, from 2018 to 2021. Secondary data were collected regarding cases of acute Chagas disease in Brazil that occurred between 2018 and 2021, where the information was collected. collected from the information technology department of the unified health system (DATASUS). The variables raised were: Region of notification, age group, sex and mode of transmission. Such information is available through the electronic address. The data obtained by TABNET/DATASUS were tabulated and analyzed in Excel version 2019. Among the 895 total cases of acute Chagas reported in the country within the period analyzed, the results showed that the occurrence of the disease was higher in males, aged between 20 and 39 years old and are more concentrated in the northern region. Furthermore, the data showed that oral contamination is the most common form of infection. Thus, it can be concluded that intensified prevention measures in regions with a higher incidence are essential for controlling the disease in this public and in society as a whole.